Genome-wide analysis and identification of microRNAs in Medicago truncatula under aluminum stress - Lu, Zhongjie; Yang, Zhengyu; Tian, Zheng; Gui, Qihui; Dong, Rui; Chen, Chao (Frontiers in Plant Science, 2023)
Numerous studies have shown that plant microRNAs (miRNAs) play key roles in plant growth and development, as well as in response to biotic and abiotic stresses; however, the role of miRNA in legumes under aluminum (Al) stress have rarely been reported. Therefore, here, we aimed to investigate the role of miRNAs in and their mechanism of Al tolerance in legumes. To this end, we sequenced a 12-strand-specific library of Medicago truncatula under Al stress. A total of 195.80 M clean reads were obtained, and 876 miRNAs were identified, of which, 673 were known miRNAs and 203 were unknown. A total of 55 miRNAs and their corresponding 2,502 target genes were differentially expressed at various time points during Al stress. Further analysis revealed that mtr-miR156g-3p was the only miRNA that was significantly upregulated at all time points under Al stress and could directly regulate the expression of genes associated with root cell growth. Three miRNAs, novel_miR_135, novel_miR_182, and novel_miR_36, simultaneously regulated the expression of four Al-tolerant transcription factors, GRAS, MYB, WRKY, and bHLH, at an early stage of Al stress, indicating a response to Al stress. In addition, legume-specific miR2119 and miR5213 were involved in the tolerance mechanism to Al stress by regulating F-box proteins that have protective effects against stress. Our results contribute to an improved understanding of the role of miRNAs in Al stress in legumes and provide a basis for studying the molecular mechanisms of Al stress regulation.